The Commander population of sea otter Enhydra lutris: history of exploitation and recovery, evaluation of modern state - Sergej V. Zagrebelniy (Известия ТИНРО, 2014)
Demographic processes within the groups of sea otter on Commander Islands (Bering and Medny Islands) are described for the period from the beginning of its recovery on Bering Island in the late 1970s. Mortality rate is proposed as an indicator of this population condition. Stable spatial and age-sex structure of sea otter on Bering Island is observed since 1999 that is accompanied by high mortality among mature animals (8 years old and elder). Density of the sea otter distribution in the coastal waters is estimated from the data on findings of dead animals. Age-sex structure of the population varies between the sites and has seasonal variation. Strained feeding conditions for the sea otter on Bering Island are defined on the materials of underwater survey conducted by the USA researchers in 2008-2009. Three ways of development are proposed for the Commander population of sea otter.